Low-protein diets with balanced amino acids reduce nitrogen excretion and foot pad dermatitis without affecting the growth performance and meat quality of free-range yellow broilers. Issue 3 (3rd July 2018) - Shao, Dan; Shen, Yiru; Zhao, Xu; Wang, Qiang; Hu, Yan; Shi, Shourong; Tong, Haibing
Abstract: An experiment was conducted to evaluate the effects of crude protein (CP) levels on growth performance, carcase quality, meat quality, immune indices, litter and faeces quality, as well as welfare quality, in free-range yellow broilers using balanced amino acid technology. In total, 600 one-d-old Suqin yellow broilers were raised for 21 d. On d 22, 540 birds with similar BW (390 ± 7 g SD) were randomly selected and placed into 9 pens (3 groups with 3 replicates per group and 60 birds each replicate) and then reared to 56 d of age. The birds were fed a diet containing CP 19% (control), 18% or 17% (measured value: 18.878%, 17.881%, 17.052%, respectively), in three groups for 35 d. The results revealed that decreasing dietary CP levels from 19% to 17% had no impact on broiler growth performance, carcase quality and meat quality ( p  > .05). The relative immune organ weights also showed no change to the lowering of dietary CP levels ( p  > .05), whereas serum albumin was significantly influenced by decreasing dietary CP levels ( p  = .042). Furthermore, nitrogen content in litter and faeces, as well as the footpad dermatitis score for welfare indices, were decreased with decreased dietary CP levels ( p  = .009, p  = .014, p  = .045, respectively). The results of this study suggest that low-protein diets with balanced amino acids reduce nitrogen excretion and footpad dermatitis without effecting the performance, carcase quality, and meat quality of free-range yellow broilers.